Respons Tanaman Jarak Pagar Terhadap Mikoriza Indigenous dan Pupuk P di Lahan Bekas Tambang Batu Bara - KARTIKA, Elis; LIZAWATI, LIZAWATI; HAMZAH, Hamzah (Universitas Jambi, 2018)
The objective of this research was to assess the response of Jatropha curcas to indigenous Arbuscular Mycorrhizal Fungi (AMF) and P fertilizers applications in former coal mine fields. This study used a single factor Randomized Block Design which is a combination of mycorrhiza and P fertilizer consisting of 10 levels (without FMA and without P fertilizer, without FMA and 25% recommended doses of P fertilizer, without FMA and 50% recommended doses of P fertilizer, without FMA and 75% recommended doses of P fertilizer, without FMA and 100% recommended doses of P fertilizer, FMA and without P fertilizer, FMA and 25% recommended doses of P fertilizer, FMA and 50% recommended doses of P fertilizer, FMA and 75% doses of P fertilizer, FMA and 100% recommended doses of P fertilizer), with recommended doses is 150 Kg SP 36 / ha The observed variables were N, P, K uptake and Jatropha curcas yield. The results showed that the symbiotic of Jatropha curcas with FMA combined with 50% recommended dose of P fertilizer gave the best N, P, K uptake and Jatropha curcas yield in Coal Post-Mining Land.